DIAGNOSIS OF EARLY FETAL DEATH USING ULTRASONOGRAPHY IN CROSSBRED CATTLE: A REPORT - LOKAVYA, ATHIDI; PATRA, M K; HITESH,; KOHLI, KALPENDRA; KUMAR, HARENDRA (The Indian Journal of Animal Reproduction, 2023)
Early foetal or late embryonic death is one of the inevitable reasons of pregnancy loss in domestic species.Ultrasonography is a potential aid to identify this condition at the earliest possible, which otherwise go unnoticed andending up increase in inter-calving interval. The present case report illustrates ultrasonographic visualization of lateembryonic and early fetal death characterized by empty amniotic vesicle, change in echogenicity of fetal fluid, foetalmembrane detachment in three Vrindavani cross bred cows at 45-75 days gestation.
Keywords: Cow; amniotic vesicle; fetal death; membrane detachment; ultrasonography